Variações diurnas da temperatura corporal, proteínas plasmáticas e eritrograma de cabras não prenhes - Yanaka, Rodrigo; Camargo, Diogo Gauber de [UNESP]; Santos, Wildemberto Arena [UNESP]; Soeiro, Carolina Soares; Viol, Milena Araúz [UNESP]; Feitosa, Francisco Leydson Formiga [UNESP]; Ciarlini, Paulo César [UNESP] (My University, 2011)
Hemogram values may have variations caused by intrinsic or extrinsic factors, which can take healthy animals to present values outside of the normal reference ranges and it is important to the veterinarian to know these variation factors for a correct results interpretation. The influence of the period of the day is among them. The objective of this study was to test the hypothesis that there are hematological parameters variations, such as erythrogram and plasmatic proteins during the day. The study was carried out with 10 non-pregnant adult goats in Araçatuba/SP/Brazil. The blood sampling and physical exam occurred at three moments between 07:00 and 08:00 a.m. (M1), 12:30 and 01:30 p.m. (M2), 5:00 and 6:00 p.m. (M3). We noted differences in the values of packed cell volume (PCV), hemoglobin, and rectal temperature through the moments, with reduction of PCV and hemoglobin were related to increase in rectal and air temperature, leading to water intake increase and, consequently, decreasing blood concentration. These variations could lead to an error of interpretation of the results due to values below the reference ranges.
Diurnal variations of body temperature, plasmatic proteins and erythrogram of non-pregnant goats
Keywords: Caprine; Circadian rhythm; Hematocrit; Rectal temperature; Caprinos; Cciclo circadiano; Hematócrito; Temperatura retal